2016 AIChE Spring Meeting & 12th Global Congress on Process Safety : process safety spotlights (Center for Chemical Process Safety/AIChE, 2016)
The session chairs are interested in papers and presentations that describe approaches or programs designed to help facilitate the communication of technical engineering concepts and/or EHS related topics to internal and external non-technical stake holders (e.g. management, employees, regulators, education, and or public forms).